Altered MicroRNA Profile in Osteoporosis Caused by Impaired WNT Signaling - Mäkitie, Riikka E; Hackl, Matthias; Niinimäki, Riitta; Kakko, Sakari; Grillari, Johannes; Mäkitie, Outi (The journal of clinical endocrinology and metabolism, 2018)
Abstract Context WNT signaling is fundamental to bone health, and its aberrant activation leads to skeletal pathologies. The heterozygous missense mutation p.C218G in WNT1, a key WNT pathway ligand, leads to severe early-onset and progressive osteoporosis with multiple peripheral and spinal fractures. Despite the severe skeletal manifestations, conventional bone turnover markers are normal in mutation-positive patients. Objective This study sought to explore the circulating microRNA (miRNA) pattern in patients with impaired WNT signaling. Design and Setting A cross-sectional cohort study at a university hospital. Participants Altogether, 12 mutation-positive (MP) subjects (median age, 39 years; range, 11 to 76 years) and 12 mutation-negative (MN) subjects (35 years; range, 9 to 59 years) from two Finnish families with WNT1 osteoporosis due to the heterozygous p.C218G WNT1 mutation. Methods and Main Outcome Measure Serum samples were screened for 192 miRNAs using quantitative polymerase chain reaction. Findings were compared between WNT1 MP and MN subjects. Results The pattern of circulating miRNAs was significantly different in the MP subjects compared with the MN subjects, with two upregulated (miR-18a-3p and miR-223-3p) and six downregulated miRNAs (miR-22-3p, miR-31-5p, miR-34a-5p, miR-143-5p, miR-423-5p, and miR-423-3p). Three of these (miR-22-3p, miR-34a-5p, and miR-31-5p) are known inhibitors of WNT signaling: miR-22-3p and miR-34a-5p target WNT1 messenger RNA, and miR-31-5p is predicted to bind to WNT1 3′UTR. Conclusions The circulating miRNA pattern reflects WNT1 mutation status. The findings suggest that the WNT1 mutation disrupts feedback regulation between these miRNAs and WNT1, providing insights into the pathogenesis of WNT-related bone disorders. These miRNAs may have potential in the diagnosis and treatment of osteoporosis. This study reports a unique serum expression pattern of eight circulating miRNAs in WNT1 mutation-positive subjects and a finding of communication between WNT1 and miR-31-5p.